NTCP model for postoperative complications and one-year mortality after trimodality treatment in oesophageal cancer. (December 2019) - Thomas, Melissa; Defraene, Gilles; Lambrecht, Maarten; Deng, Wei; Moons, Johnny; Nafteux, Philippe; Lin, Steven H.; Haustermans, Karin
Highlights: Around 20–30% of oesophageal cancer patients develop a postoperative complication after trimodality treatment. An NTCP model for postoperative pulmonary complications included mean lung dose. An NTCP model for one-year mortality included lung absolute V35 . NTCP models can be used to select patients who might benefit from proton therapy. Abstract: Purpose/Objectives: To develop normal tissue complication probability (NTCP) models for postoperative pulmonary and cardiac complications and one-year mortality after preoperative chemoradiotherapy and surgery in oesophageal cancer patients. Methods: 691 patients from two institutions (2002–2017) were included; 134 treated with protons. Multivariable logistic regression analyses on 601 patients studied the predictive value of clinical/treatment-related (gender, age, body mass index (BMI), smoking, cardiac comorbidity, chronic obstructive pulmonary disease, histology, cT/N) and dosimetric variables (absolute/relative lung/heart volumes receiving or spared from xGy, mean doses, planning target volume) for the presence of pulmonary complications, cardiac complications and one-year mortality. Model validation was performed using a nonrandom split-sample of 90 patients. Model performance was assessed by AUC and calibration plots. Results: Respectively 144/601 (24.0%) and 165/601 (27.5%) patients developed a pulmonary or cardiac complication. For pulmonary complications, an NTCP model with optimism-corrected AUC of 0.75 (95%CI = 0.73–0.76) was obtained. The model contained mean lung dose (OR = 1.15, 95%CI = 1.09–1.22, p  < 0.001), increasing age (OR = 1.03, 95%CI = 1.01–1.06, p  = 0.002), BMI (OR = 1.04, 95%CI = 0.99–1.08, p  = 0.084) and squamous cell carcinoma (OR = 3.22, 95%CI = 1.97–5.24, p  < 0.001) as predictors. In validation, AUC of 0.79 was obtained (calibration slope 1.26). For cardiac complications, only age (OR = 1.06, 95%CI = 1.04–1.09, p  < 0.001) with optimism-corrected AUC of 0.67 (95%CI = 0.65–0.68) was selected. For one-year mortality, an NTCP model with optimism-corrected AUC of 0.63 (95%CI = 0.58–0.66) was obtained. Lung absolute V35 (OR = 1.0016, 95%CI = 1.0007–1.0026, p  = 0.001), cN (OR = 2.45, 95%CI = 1.18–5.09, p  = 0.017), cT4 (OR = 2.51, 95%CI = 1.10–5.74, p  = 0.029) and cardiac comorbidity (OR = 2.91, 95%CI = 1.46–5.77, p  = 0.002) were selected as predictors. At validation, AUC of 0.57 was obtained (calibration slope 0.75). Conclusion: We were able to build and validate NTCP models for the presence of a postoperative pulmonary complication and for one-year mortality after trimodality treatment in oesophageal cancer.